Study Environment and Psychological Factors of University Students’ Intention to Drop out - Bulotaitė, Laima; Sargautytė, Rūta; Žukauskaitė, Irena; Bagdžiūnienė, Dalia (Acta Paedagogica Vilnensia, 2025)
Student dropout is a pressing issue demanding immediate attention from most universities. It profoundly affects the psychological well-being of students, their financial status, career path, relationship with others while also raising concerns within the university about the quality of studies, study programs, academic personnel, resource reallocation or reputation management. Furthermore, dropout can impact the students’ close relatives and even society at large, which may face a shortage of skilled professionals in the future.Our study aims to uncover the relationship between the study environment and psychological factors, and university students’ dropout intentions with the potential to provide valuable insights which would enable the development of effective preventive measures and programs.350 university students (of whom, 20% males and 80% females) participated in the study. The participants filled out a questionnaire measuring Study engagement (Schaufeli et al., 2019), Academic resilience (Martin & Marsh, 2006), Study satisfaction (Schmitt et al., 2008), Study environment characteristics (autonomy, feedback, support from teachers and students, and opportunities for development) (Bakker, 2014), Study-related stress, Intention to drop out, along with questions on sociodemographic data.The results show that study engagement is predicted by academic resilience, satisfaction with studies, and study environment factors. Study-related factors, student engagement, and stress predict the dropout intention. Moreover, it was discovered that study engagement mediates the effect of academic resilience, student satisfaction and study environment factors on dropout intention. Study-related stress has a direct positive effect on the intention to drop out. The results of the study confirmed that study environment factors (autonomy, feedback, teacher and student support, and development opportunities) together with psychological characteristics (student engagement, academic resilience, study satisfaction and study-related stress) are important predictors of students’ intention to drop out.These aspects are important to consider when developing and implementing preventive programs and measures to manage students’ dropout from universities.
Keywords: university students; intention to drop out; student engagement; study environment; psychological factors